The Word “Woman” in Pre-Modern Arabic Lexicons: From the Kitāb al-ʿAyn to the Lisān al-ʿArab - Paraskeva, Tsampika (Hawwa, 2021)
Abstract In all languages, lexicons constitute a valuable source of information on femininities and women. This assertion is enhanced in the case of pre-modern Arabic lexicography, due to the diversity of its contents. However, the picture of women in lexicons has always received more attention in the field of lexicography in Western languages than in Arabic. This paper aims to fill a minor part of this noteworthy gap, by shedding light on all semantical, lexical, and orthographic elements which concern the word “woman” (imraʾa/al-marʾa) in pre-modern Arabic lexicons, more specifically, under the root m-r-ʾ.